A SURVEY OF PAPR REDUCTION IN OFDM SIGNALS - SRIDEVI, A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Â  In Radio waves, the digital data can be transmitted using Burst number of data using OFDM technique. So only an OFDM Technique is called attractive modulation techniques. In this OFDM signal transmission having so many disadvantages, one of the main disadvantages is a Peak average power which is due to combination of sinusoidal leads to high peak-to power ratio (PAPR).Due to High PAPR, which leads to poor (i.e) degrades the signal performance of power amplifier in transmission, this PAPR can be reduce using some of the following technique like, there are Clipping, Coding, Partial transmit sequence (PTS), Sequential Mapping(SM), Tone reservation (TR), Tone injection (TI), Interleaving, Nonlinear companding transform, & Hadamard transform etc.Various technique are available to reduce the Peak power and discuss detail about the merits and demerits .Â 